Effect of Customization Options on Consumer Satisfaction in Fashion Retail in Vietnam - Linh, Pham (International Journal of Fashion and Design, 2024)
Purpose: The aim of the study was to analyze the effect of customization options on consumer satisfaction in fashion retail in Vietnam. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Customization options in fashion retail have a significant impact on consumer satisfaction in Vietnam. The ability for customers to personalize their clothing and accessories according to their preferences enhances their shopping experience. Studies have shown that 70% of Vietnamese consumers prefer brands that offer customization due to the perceived uniqueness and personal value of the products. Retailers providing customization options often see higher customer satisfaction rates, as this approach caters to individual tastes and needs, leading to increased loyalty and repeat purchases. Unique Contribution to Theory, Practice and Policy: Theory of planned behavior (TPB), self-determination theory (SDT) & expectation-confirmation theory (ECT) may be used to anchor future studies on effect of customization options on consumer satisfaction in fashion retail in Vietnam. Fashion retailers should invest in advanced customization tools that allow for seamless and enjoyable customization experiences. Industry bodies and policymakers should work towards standardizing customization practices across the fashion retail sector.